A Pressure-Correction Scheme for Rotational Navier-Stokes Equations and Its Application to Rotating Turbulent Flows (Communications in Computational Physics, 2011)
The rotational incremental pressure-correction (RIPC) scheme, described inTimmermans et al. [Int. J. Numer. Methods. Fluids., 22 (1996)] and Shen et al. [Math.Comput., 73 (2003)] for non-rotational Navier-Stokes equations, is extended to rotatingincompressible flows. The method is implemented in the context of a pseudoFourier-spectral code and applied to several rotating laminar and turbulent flows.The performance of the scheme and the computational results are compared to the so-calleddiagonalization method (DM) developed by Morinishi et al. [Int. J. Heat. Fluid.Flow., 22 (2001)]. The RIPC predictions are in excellent agreement with the DM predictions,while being simpler to implement and computationally more efficient. TheRIPC scheme is not in anyway limited to implementation in a pseudo-spectral code orperiodic boundary conditions, and can be used in complex geometries and with othersuitable boundary conditions.